Physiopathological bases of the pain - Zegarra Piérola, Jaime Wilfredo (2024)
Pain is a sign of illness and a common complain that bring patients to a health care facility. It is classified in acute or chronic pain, nociceptive or neuropathic, and according to conduction velocity, fast or slowly. C and Aδ- fibers respond to stimuli and produce the experience of pain, this defines them as nociceptors. Central pathways of pain include: nociceptors respond to stimuli and produce the experience of pain when they are electrically stimulated (Transduction); axons of nociceptors enter the spinal cord via the dorsal root, where Glutamate are Substance P are released, spinal neurons send their axons to the contralateral thalamus (Transmission); the perceived intensity of pain can be modulated by brain circuits (Modulation). Pain inhibition is achieved by calcium channel blockage and open potassium channel by endogenous and exogenous opioids, due hyperpolarization of the cell and inhibition of pain mediators. b endorphins, enkephalins and dinorphins are released due to activation of neural descending pathway causing pain relief.